Knockdown of lncRNA KCNQ1OT1 suppresses the adipogenic and osteogenic differentiation of tendon stem cell via downregulating miR-138 target genes PPARγ and RUNX2. Issue 19 (18th October 2018) - Yu, Yang; Chen, Ying; Zhang, Xiaolei; Lu, Xiaolang; Hong, Jianjun; Guo, Xiaoshan; Zhou, Dongsheng
ABSTRACT: The study aimed to investigate the mechanism and biological roles of long noncoding RNA KCNQ1OT1 in adipogenic and osteogenic differentiation of tendon stem cell. In this study, tendon injury mice model was established to detect the expression of lncRNA KCNQ1OT1, miR-138, peroxisome proliferator-activated receptor gamma (PPARγ) and runt-related gene 2 (RUNX2) using quantitative real-time PCR (qRT-PCR) and western blot. Mechanical testing was carried out to assess tendon function. Adiponectin and Osterix were used to evaluate the adipogenic and osteogenic differentiation of tendon stem cells (TSCs). The interaction between lncRNA KCNQ1OT1 and miR-138 was detected by RNA immunoprecipitation (RIP) assay and RNA pull-down assay. We found that lncRNA KCNQ1OT1, PPARγ and RUNX2 expression were significantly upregulated, while miR-138 was suppressed in tendon tissue of injured group and the separated TSCs. lncRNA KCNQ1OT1 knockdown inhibited the adipogenic and osteogenic differentiation of TSCs. Further studies indicated that lncRNA KCNQ1OT1 functioned as a competing endogenous RNA (ceRNA) by sponging miR-138 in TSCs. Further investigations confirmed that lncRNA KCNQ1OT1 knockdown exerted anti-adipogenic and anti-osteogenic function via miR-138/PPARγ and miR-138/RUNX2 axis. Therefore, the lncRNA KCNQ1OT1/miR-138/PPARγ or RUNX2 axis modulated adipogenic and osteogenic differentiation of tendon stem cell, which might be a promising therapeutic target for tendon injuries.